Integrating Innovative Experiential Learning in Cyclic Teaching Sessions of English Speaking Classes - Ida Bagus Nyoman Mantra; I Nengah Astawa; Ida Ayu Made Sri Widiastuti (Politeknik Negeri Bali, 2018)
The ability to speak English confidently and effectively has been valued as the most essential competence in international communication. The present study is aimed at improving English learners’ speaking skill through the integration of experiential learning. A classroom action research was conducted in two consecutive cyclic learnings, consisted of four thematic learning sessions. The data for this study were collected by administering a pre-test to figure out the initial reflection of the students’ speaking skill, and post-test was conducted by the end of each cycle to find out the improvement of the students’ speaking skill after the implementation of Experiential Learning in speaking classes. A set of questionnaires was also administered to reveal the changing behavior of the English learners after learning to speak through experiential learning. The mean score in the first and second cycles showed the improvement of the students’ speaking skill compared to mean score of the pre-test. This indicated that the English learners’ speaking skill could be significantly improved through the implementation of Experiential Learning.